Perceptions of adolescents concerning health promotion: their contributions to nursing - Paula, Jordana Aparecida; Melo, Maria Carmen Simões Cardoso; Amorim, Thaís Vasconselos; Salimena, Anna Maria de Oliveira; Paiva, Andyara do Carmo Pinto Coelho; Nascimento, Rômulo Cândido Nogueira (Revista Cuidarte, 2020)
Introduction: Adolescents represent an important part of the population with lifestyle-related specificities, which is why actions to promote healthy habits are required. In this view, understanding the perceptions that influence typical adolescent health behaviors becomes essential for health and nursing care, considering that self-care decisions are marked by singularities. Objective: To expose the perceptions of adolescents regarding self-care in the context of health promotion and nursing. Materials and Methods: A Heideggerian phenomenological research approach with 17 adolescents from a public school in Minas Gerais was conducted between October and December 2016. The analytical hermeneutic movement allowed the appearance of the phenomenon under study. Results: On self-care, adolescents expressed that they see a doctor only when needed; they know that they have to take care of their health, but not to exercise or eat healthy and take care of their health now, but because it may be an issue in the future. 68% of the participants reported being physically active during PE classes and 30% reported drinking alcohol. Discussion and Conclusions: When understanding adolescents' perceptions on self-care, nurses find more elements to carry out health actions aimed at stimulating healthy behaviors that will lead to a better quality of life in the present and the future.Como citar este artigo: Paula JA, Melo MCSC, Amorim TV, Salimena AMO, Paiva ACPC, Nascimento RCN. Subjetividades de adolescentes face à promoção da saúde: contribuições para a enfermagem. Rev Cuid. 2020; 11(1): e895. http://dx.doi.org/10.15649/cuidarte.895
Keywords: Adolescent Health; Nursing Care; Health Promotion